Update on infections caused by Stenotrophomonas maltophilia with particular attention to resistance mechanisms and therapeutic options - Chang, Ya Ting; Lin, Chun Yu; Chen, Yen Hsu; Hsueh, Po-Ren (Frontiers in Microbiology, 2015)
Stenotrophomonas maltophilia is a Gram-negative, biofilm-forming bacterium. Although generally regarded as an organism of low virulence, S. maltophilia is an emerging multi-drug resistant opportunistic pathogen in hospital and community settings, especially among immunocompromised hosts. Risk factors associated with S. maltophilia infection include underlying malignancy, cystic fibrosis, corticosteroid or immunosuppressant therapy, the presence of an indwelling central venous catheter and exposure to broad spectrum antibiotics. In this review, we provide a synthesis of information on current global trends in S. maltophilia pathogenicity as well as updated information on the molecular mechanisms contributing to its resistance to an array of antimicrobial agents. The prevalence of S. maltophilia infection in the general population increased from 0.8%-1.4% during 1997-2003 to 1.3%-1.68% during 2007-2012. The most important molecular mechanisms contributing to its resistance to antibiotics include β-lactamase production, the expression of Qnr genes, and the presence of class 1 integrons and efflux pumps. Trimethoprim/sulfamethoxazole (TMP/SMX) is the antimicrobial drug of choice. Although a few studies have reported increased resistance to TMP/SMX, the majority of studies worldwide show that S. maltophilia continues to be highly susceptible. Drugs with historically good susceptibility results include ceftazidime, ticarcillin-clavulanate, and fluoroquinolones; however, a number of studies show an alarming trend